The Influence of Job Performance, Social Security, and Employee Incentives on Employee Job Satisfaction Mathematical Multicollinearity Test Method - Irawan, Dedi; Hendrikson R Panjaitan; Surya Wisada Dachi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This research aims to determine the significant influence of work performance, social security and employee incentives on employee job satisfaction. This research was carried out using quantitative research. The population in this research was 35 with 35 samples taken. The sampling technique in this research used a total sampling technique. This research used secondary data obtained from distributing questionnaires. Using the Multiple Regression Analysis method, using SPSS 22. Based on the results of the first hypothesis test, it is known that the significant value of work performance is 3.894 > 2.03951. The work performance variable has a significant influence on the employee job satisfaction variable. The second hypothesis shows that social security has a significant value of 0.477 < 2.03951, meaning that the social security variable has no significant influence on the employee job satisfaction variable. The third hypothesis shows that employee incentives are significant, namely 2.510 > 2.03951, meaning that the employee incentive variable has a significant influence on the employee job satisfaction variable. The fourth hypothesis shows a significant Fcount value of 20.093 which is compared to Ftable of 2.90 (20.093 > 2.90), meaning that the variables of work performance (X1), social security (X2) and employee incentives (X3) simultaneously have a significant influence. with employee job satisfaction variables